Prototype GA-enhanced multi-objective dynamic scheduler for multiple shop floors - Yin, Xiaofeng. (2008)
This thesis describes the development of a prototype genetic algorithm (GA)-enhanced multi-objective dynamic scheduler for multiple shop floors. A framework of the prototype scheduler, which accepts data input from a scheduling database or a formatted file and outputs a near-optimal schedule, is proposed.